PENGARUH SERVICE QUALITY DAN PRODUCT QUALITY TERHADAP LOYALITAS PELANGGAN SERTA DAMPAKNYA PADA REPEAT ORDER DI ASTRA CREDIT COMPANIES CABANG MAKASSAR - Sumiati Sumiati; Buyung Romadhoni; Muhammad Adil (COMPETITIVENESS, 2022)
This research aims to find out the influence: (1) service quality on customer loyalty, (2) product quality on customer loyalty, (3) service quality on repeat orders, (4) product quality on repeat orders, (5) customer loyalty to repeat orders, (6) service quality to repeat orders through customer loyalty, (7) product quality to repeat orders through customer loyalty. The problem in this study is the extent to which service quality and product quality affect customer loyalty and its impact on repeat orders in ACC Makassar Branch. This study uses quantitative methods, sample withdrawal with Accidental Sampling, data collection techniques using online questionnaires shared with 100 customers of ACC Makassar Branch.  Hypothesis testing using Path Analysis with the help of AMOS 21 software.Test results show that service quality and product quality have a significant positive effect on customer loyalty and have a significant direct effect on repeat orders and have a significant effect on repeat orders through customer loyalty, customer loyalty has a significant positive effect on repeat orders. Based on the results of the research, it is recommended that ACC Makassar Branch can create and improve product quality with down payment and rate that is different from competitors and provide adequate parking space for the creation of customer loyalty that will have an impact on increasing repeat orders.                                                                                                   Keywords: Service Quality, Product Quality, Customer Loyalty, Repeat Order.